Der Kernbestandsschutz der Unionsbürgerschaft - Neier, Christina (Schriftenreihe Europäisches Recht, Politik und Wirtschaft, 2019)
Traditionally, the application of EU citizenship rights is conditioned on the existence of a cross-border element. In the two landmark decisions Rottmann and Ruiz Zambrano, the CJEU deviated from this traditional approach. According to this case law, EU citizens are protected by EU law in situations in which they lose their EU citizenship or are, in fact, forced to leave the territory of the Union even if they have not exercised their right to move. With this new doctrine, the step from the "cross border paradigm" to the "status paradigm" is taken. This study provides a doctrinal structure of the CJEU case law and explores the underlying general guarantee in order to clarify the scope and potential of this new concept in EU citizenship law. This book is therefore likely to be of interest to both practitioners and legal scholars.